Variation in Antiosteoporotic Drug Prescribing and Spending Across Spain. A Population-Based Ecological Cross-Sectional Study - Sanfélix-Gimeno, Gabriel; Librero-López, Julián; Modroño-Riaño, Gracia; Peiró, Salvador; Rodríguez-Bernal, Clara L. (Frontiers in Pharmacology, 2018)
Introduction: Evidence has shown that utilization of antiosteoporotics does not correspond with risk, and studies on other therapies have established geographic differences in adequacy of pharmaceutical prescribing. Nevertheless, the variability in osteoporotic drug consumption is understudied. We aimed to describe variations in pharmaceutical utilization and spending on osteoporotic drugs between Health Areas (HA) in Spain. Methods: Population-based cross-sectional ecological study of expenditure and utilization of the five therapeutic groups marketed for osteoporosis treatment in Spain in 2009. Small area variation analysis (SAVA) methods were used. The units of analysis were the 168 HA of 13 Spanish Regions, including 7.2 million women aged 50 and older. The main outcomes were the Defined Daily Dose (DDD) per 1000 inhabitants and day (DDD/1000/Day) dispensed according to the pharmaceutical claims reimbursed, and the expenditure on antiosteoporotics at retail price per woman ≥50 years-old and per-year. Results: The average osteoporosis drug consumption was 116.8 DDD/1000W/Day, ranging from 78.5 to 158.7 DDD/1000W/Day between the HAs in the 5th and 95th percentiles. Seventy five percent of the antiosteoporotics consumed were bisphosphonates, followed by raloxifene, strontium ranelate, calcitonins and parathyroid hormones. Regarding variability by therapeutic groups, biphosphonates showed the lowest variation, while calcitonins and parathyroid hormones showed the highest variation. The annual expenditure on antiosteoporotics was € 426.5 million, translating into an expenditure of € 59.2 per woman and varying between € 38.1 and € 83.3 between HAs in the 5th and 95th percentiles. Biphosphonates, despite accounting for 79% of utilization, only represented 63% of total expenditure, while parathyroid hormones with only 1.6% of utilization accounted for 15% of the pharmaceutical spending. Conclusions: : This study highlights a marked geographical variation in the prescription of antiosteoporotics, being more pronounced in the case of costly drugs such as parathyroid hormones. The differences in rates of prescribing explained almost all of the variance in drug spending, suggesting that the difference in prescription volume between territories, and not the price of the drugs, is the main source of variation in this setting. Data on geographical variation of prescription can help guide policy proposals for targeting areas with inadequate antiosteoporotic drug use.